In Search of Enzymes with a Role in 3′, 5′-Cyclic Guanosine Monophosphate Metabolism in Plants - Gross, Inonge; Durner, Jörg (Frontiers in Plant Science, 2016)
In plants, nitric oxide-mediated 3′, 5′- cyclic guanosine monophosphate (cGMP) synthesis plays an important role during pathogenic stress response, stomata closure upon osmotic stress, the development of adventitious roots and transcript regulation. The nitric oxide-cGMP dependent pathway is well characterized in mammals. The binding of nitric oxide to soluble guanylate cyclase enzymes (GCs) initiates the synthesis of cGMP from guanosine triphosphate. The produced cGMP alters various cellular responses, such as the function of protein kinase activity, cyclic nucleotide gated ion channels and cGMP-regulated phosphodiesterases. The signal generated by the second messenger is terminated by 3′, 5′- cyclic nucleotide phosphodiesterase (PDEs) enzymes that hydrolyze cGMP to a non cyclic 5′- guanosine monophosphate. To date, no homologues of mammalian cGMP-synthesizing and degrading enzymes have been found in higher plants. In the last decade, six receptor proteins from Arabidopsis thaliana have been reported to have guanylate cyclase activity in vitro. Of the six receptors, one was shown to be a nitric oxide dependent guanylate cyclase enzyme (NOGC1). However, the role of these proteins in planta remains to be elucidated. Enzymes involved in the degradation of cGMP remain elusive, albeit, PDE activity has been detected in crude protein extracts from various plants. Additionally, several research groups have partially purified and characterized PDE enzymatic activity from crude protein extracts. In this review, we focus on presenting advances toward the identification of enzymes involved in the cGMP metabolism pathway in higher plants.